Política pública de inclusão escolar no Estado do Paraná: e sua implementação no município de Cascável-PR - Ogura, Anália Fiorini (2002)
The purpose of this study is to know about the Educational Politic of Scholar Inclusion in Paraná state that has been implemented. To identify and compare the conception that teachers from regular studies in Cascavel have about scholar inclusion, with the conception from Paraná state. In order to do that, we investigate teachers from municipal and state departments in Cascavel and we used a mixed questionnaire as an instrument to get the data. In the first chapter, we discussed the Brazilian Public Politics for Educational Scholar Inclusion process based on literatures of different conceptions about the current legislation and more specifically about the movement of scholar inclusion process. The study demonstrated the legal aspect from everyone s rights , the state duty and the aspect in which the scholar inclusion is related to the physical structure adaptation from the curriculum and teaching capacity. In the second chapter, we analyses the implementation in Cascavel, during the last 5 years, the Inclusion Politics from Paraná State. We discussed and analised the previous document Paraná s Scholar Inclusion Proposition , originated from different scientific meetings. We found out that Paraná State is working in order to accomplish the Educational Including Politics toward fair, public and democratic education. Indeed, they want to assure the socialization of educational knowledge the most, as a cultural instrument necessary to the student plays a role in the social practice. In the third chapter, we presented the results. About teacher s graduation the results showed that 55% had superior level and 45% had professorship during high school. The teaching system in which Cascavel teachers work, the majority of them belongs to municipal departments (47%, followed by the State department (35%) and private institutions (18,%). About the improvement way used by the state, municipal and private institutions to teachers graduation, it was clear that there was a large concentration of lectures, followed by seminaries, forum and courses, related to the promotion of this activities, we found out that the state (49%) was the one which promoted more meetings, followed by the municipal (36%) and the private organizations (15%). The distribution of the places by the state wasn t uniform because some regions were privileged. They are Faxinal do Céu (38%), Cascavel (32%), Foz do Iguaçu (11%), Londrina (6%), Curitiba (8%) and Medianeira (5%). To clarify about the inclusion done during these events, the majority (84,5%) answered that it wasn t enough and they justified in several ways, although (15,5%) affirmed that the clarification wasn t enough. As the state s role in the process of educational inclusion, teachers had their point of view in a clear and precise way. Concerning to time that schools are working toward the scholar inclusion varied between 1 and 4 years. According to the financial resources sent by Paraná state to the implementation of the scholar inclusion politic, they are short according to 38% of the researchers. The conception about the definition of scholar inclusion, we verified that 85% of the teachers know it, which goes to Paraná state concept. As the existence of a conception that a student who has certain special educational needs, when they are included in a regular school they will be discriminated among their peers, verifying that 56% of the teachers answered that there wasn t discrimination from the moment the teacher knows how to cope with the situation. Our analyses demonstrated that the scholar inclusion demands improvement on teacher s graduation to its implementation. Besides, the school itself has to be changed in organic significant changes to deal with demanding concerning to an education to human diversity.